Safety, Health and Feasibility Local Wisdom and Regulation of Marine Products: Convergence and Case Study of Mare Island, Tidore Islands - Husen Alting; Suwarti Suwarti; Irfan Ahmad (Journal of Global Pharma Technology, 2020)
Purpose: to finds a convergence between the local regulation and wisdom in Mare regarding the sustainability of resources and marine products and its safety, feasibility and health standards. Methods: this study is a descriptive qualitative study which describes regulations on the safety, feasibility and health standards of processing seafood and local wisdom regarding the preservation of marine resources. Result: Local wisdom in Mare has not been able to achieve regulations related to safety, feasibility and health standards of seafood but the local wisdom was able to maintain the sustainability of marine resources. Both of these things can be converged with technology so that the sustainability of marine resources can be achieved while realizing the safety, feasibility and health standards of marine produce. Conclusion: local wisdom is not a static thing so that between local wisdom and the preservation of marine resources and safety regulations, feasibility and health standards of seafood can be converged upon them.